Speech Ethics and Aesthetics: The Key Criteria of Oratorical Responsibility - Umrzokova Aida Obidjonovna (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA’LIMNING INNOVATSION YO’NALISHLARI, 2025)
Nowadays, as in neighboring countries, the development of oratory as a field rooted in national spirit, values, and traditions, and the integration of this discipline into higher education as a distinct philological subject, is one of the core tasks before the advocates of national spirituality. This article examines the ethics and aesthetics of speech, as well as the main criteria for an orator‘s responsibility. It emphasizes the modern relevance of oratory, explores effective techniques of its application, and analyzes key factors in the development of an orator, including audience engagement, clarity, credibility, persuasiveness, and emotional appeal. Based on psychological studies, the article underlines that a modern orator must approach speech with a high degree of responsibility, relying on the principles of ethics and aesthetics to ensure maximum impact.